Employee Relations Practices, Organisational Citizenship Behavior and Performance of Selected Oil Firms in Delta State, Nigeria - Godbless, Eromafuru, Edward; Joseph, Igiagbe, Ikpea (Journal of Posthumanism, 2025)
This study examined the impact of employee relations and organizational citizenship behaviour (OCB) on the performance of oil firms in Delta State, Nigeria. the objectives of the study was to ascertain the effect og employee relations on performance of selected oil firms, determine the effect of organizational citizenship behaviour on the performance of selected oil firms and mediation effect of organizational citizenship behaviour on employee relations and performance of selected oil firms in Delta State. A cross-sectional research design was adopted, with a sample of 178 staff members selected using Taro Yamane’s formula. Data were collected through structured questionnaires and analyzed using descriptive and inferential statistics. The findings revealed that employee relations have a significant positive correlation with firm performance (r = 0.469), while OCB showed a stronger positive correlation (r = 0.672). Additionally, OCB served as a mediator between employee relations and performance (r = 0.286). The study concluded that fostering both employee relations and OCB can significantly enhance organizational performance. It recommended that oil firms invest in employee relations programs, promote OCB traits, and integrate OCB into their employee relations strategies for optimal performance outcomes.